Optimizing the feeding frequency to maximize the production of sterile males in tsetse mass-rearing colonies. - Soumaïla Pagabeleguem; Ange Irénée Toé; Sié Hermann Pooda; Kiswendsida Mikhailou Dera; Abdou Salam Belem; Adrien Marie Gaston Belem; Gisèle Marie Sophie Ouedraogo/Sanou; Mamadou Ira; Bénéwendé Aristide Kaboré; Lassané Percoma; Issa Sidibé (PLoS ONE)
Tsetse flies are cyclical vectors of trypanosomes, the causative agents of sleeping sickness or Human African Trypanosomosis and nagana or African Animal Trypanosomosis in Sub-Saharan Africa. The Insectarium de Bobo-Dioulasso (IBD) was created and equipped in the frame of Pan African Tsetse and Trypanosomosis Eradication Campaign (PATTEC) with the main goal to provide sterile males for the different eradication programs in West Africa which is already the case with the ongoing eradication program in Senegal. The aim of this study was to identify the best feeding regime in mass-rearing colonies of Glossina palpalis gambiensis to optimize the yield of sterile males. We investigated the mortality and fecundity for various feeding regimes and day alternation (3×: Monday-Wednesday-Friday, 4×: Monday-Wednesday-Friday-Saturday, 4×: Monday-Wednesday-Thursday-Friday and 6×: all days except Sunday) on adult tsetse flies in routine rearing over 60 days after emergence. The day alternation in the 4 blood meals per week (feeding regimes 2 and 3) had no effect on tsetse fly mortality and fecundity. The best feeding regime was the regime of 4 blood meals per week which resulted in higher significant fecundity (PPIF = 2.5; P = 0.003) combined with lower mortality of females (P = 0.0003) than the 3 blood meals per week (PPIF = 2.0) and in similar fecundity (PPIF = 2.6; P = 0.70) and mortality (P = 0.51) than the 6 blood meals per week. This feeding regime was extended to the whole colonies, resulting in an improved yield of sterile males for the ongoing eradication program in Senegal and would be more cost-effective for the implementation of the next-coming sterile insect technique (SIT) programs in West Africa.